The effect of consumer perceptions towards intention to buy air tickets online in Malaysia - Lee, Kwee-Fah; Haque, A. K. M. Ahasanul; Maulan, Suharni (2017)
Abstract As the airline industry struggles to be profitable in the face of high operating costs and intense competition, electronic ticketing has emerged to be an effective way to reduce costs. While market research shows an increasing trend among travellers to book air tickets online, they are mostly from advanced nations such as the United States and United Kingdom. Online booking is somewhat lower in Malaysia. To increase online ticket purchases in Malaysia, it is imperative to understand the factors that influence consumers’ buying intention. Academic research remains limited in Malaysia. Therefore, this paper reviews the literature on the main variables influencing online buying intention. It starts with an overview of the airline business environment, and air travellers’ behaviour pertaining to tickets booking. Subsequently, the Technology Acceptance Model and its relevant variables are discussed. Next, the research methodology and conceptual model are presented. Finally, the paper concludes with recommendations for airline companies.